Production of Biochar from Sugarcane Bagasse using a One-Stage Pyrolysis Method for Crystal Violet Adsorption in Aqueous Environment - Vi, Vo Thuy; Quang, Tran Minh; Hoa, Bui Thi; Vuong, Bui Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4, 2025)
Biochars were prepared by anaerobic heating of sugarcane bagasse at different temperatures of 400 °C, 500 °C, 600 °C, and 700 °C for 3 hours. The biochar samples, denoted as biochar-400 o C, biochar-500 o C, biochar-600 o C, and biochar-700 o C, were used to adsorb crystal violet dye in an aqueous medium. Physico-chemical methods such as XRD, FTIR, BET, and SEM were used to evaluate the synthesized biochar materials. The concentration of crystal violet solutions was determined using UV-Vis spectroscopy at the maximum absorption wavelength of 590 nm. The results showed that the biochar samples had good adsorption capacity for crystal violet dye, with the maximum adsorption capacity of biochar-400 o C, biochar-500 o C, biochar-600 o C, and biochar-700 o C being 154.6, 160.8, 182.8, and 168.6 mg/g, respectively. The biochar-600 o C sample has the highest adsorption capacity, consistent with its physico-chemical properties such as the highest porosity and specific surface area. Therefore, the cheap and simple prepared biochar has great potential to be used as an adsorbent material to remove crystal violet dye in an aqueous environment.